2011
DOI: 10.1111/j.1365-3156.2011.02757.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful application of a simple specimen transport method for the conduct of respiratory virus surveillance in remote Indigenous communities in Australia

Abstract: Summaryobjective Surveillance programs and research for acute respiratory infections in remote Aboriginal communities are complicated by difficulties in the storage and transport of frozen samples to urban laboratories for testing. This study assessed the sensitivity of a simple method for transporting respiratory samples from a remote setting for viral PCR compared with frozen specimens.methods We sampled every individual who presented to a remote Aboriginal community clinic in a non-epidemic respiratory seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 21 publications
0
37
1
Order By: Relevance
“…Our study has demonstrated that freezing of specimens for viral studies at the time of collection is not required, [6] however the detection of common respiratory bacteria is affected, with lower detection rates in mailed specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has demonstrated that freezing of specimens for viral studies at the time of collection is not required, [6] however the detection of common respiratory bacteria is affected, with lower detection rates in mailed specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex polymerase chain reaction (PCR) was used to test for adenovirus, respiratory syncytial virus (RSV) groups A and B, influenza virus types A and B, parainfluenza virus types 1–3, human metapneumovirus, human rhinoviruses, human coronaviruses (OC43, 229E,NL63 + HKU1), human bocavirus, human polyomaviruses KI and WU, M. pneumoniae, C. pneumoniae, B. pertussis, S. pneumoniae , S. aureus, non-typeable Haemophilus influenzae (NTHi) and M. catarrhalis using previous established methods [11, 12]. …”
Section: Methodsmentioning
confidence: 99%
“…Parents mailed the swabs to the Queensland Paediatric Infectious Diseases Laboratory, where the swabs were immediately stored at −80°C until tested. Qualitative real‐time PCR was performed for Influenza A and B and other 13 respiratory viruses . This method is well established and short delays between swab collection and processing in the laboratory do not impact on the likelihood of identifying any/total respiratory virus(es) from nasal swabs …”
Section: Methodsmentioning
confidence: 99%